Sensitization to Cockroach Allergen: Immune Regulation and Genetic Determinants - Peisong Gao (Clinical and Developmental Immunology)
Asthma is a major public health concern. Cockroach allergen exposure and cockroach allergic sensitization could contribute to the higher prevalence of asthma. However, the underlying immune mechanism and the genetic etiology remain unclear. Recent advances have demonstrated that several receptors (PAR-2, TLRs, CLRs) and their pathways mediate antigen uptake from the environment and induce allergies by signaling T cells to activate an inappropriate immune response. Cockroach-derived protease can disturb airway epithelial integrity via PAR-2 and leads to an increased penetration of cockroach allergen, resulting in activation of innate immune cells (e.g., DCs) via binding to either TLRs or CLRs. The activated DCs can direct cells of the adaptive immune system to facilitate promotion of Th2 cell response and subsequently increase risk of sensitization. Mannose receptor (MR), as a CLR, has been shown to mediate Bla g2 (purified cockroach allergen) uptake by DCs and to determine allergen-induced T cell polarization. Additionally, genetic factors may play an important role in conferring the susceptibility to cockroach sensitization. Several genes have been associated with cockroach sensitization and related phenotypes (HLA-D, TSLP, IL-12A, MBL2). In this review, we have focused on studies on the cockroach allergen induced immunologic responses and genetic basis for cockroach sensitization.